Genomics in non-adenoid cystic group of salivary gland cancers: one or more druggable entities?. (4th May 2019) - Cavalieri, Stefano; Platini, Francesca; Bergamini, Cristiana; Resteghini, Carlo; Galbiati, Donata; Bossi, Paolo; Perrone, Federica; Tamborini, Elena; Quattrone, Pasquale; Licitra, Lisa; Locati, Laura Deborah; Alfieri, Salvatore
ABSTRACT: Introduction : Salivary gland cancers (SGCs) are a rare and heterogeneous group of malignant tumors arising from either major or minor salivary glands. Among SGCs patients, adenoid cystic carcinoma (ACC) is the most frequent histotype and its genetic aberrations are well known even though they are generally uncommon. Non-ACC subtypes are rarer and more heterogeneous than ACC from a histological and genomic point of view. In non-ACC, some altered molecular pathways [e.g. BRAF or RET mutations, Androgen Receptor (AR)] are potentially targetable with specific drugs. Areas covered : A literature search was performed to summarize the main druggable genomic aberrations involving non-ACC SGCs. An overview of the genomics of non-ACC salivary gland malignancies is discussed. We describe the pattern of potentially targetable genomic alterations in non-ACC salivary gland malignancies according to their frequency rather than to the single non-ACC histotype. Expert opinion/commentary : The genetic profiling through in-depth molecular analyses [e.g. Next-generation sequencing (NGS)] is advised in all patients affected by recurrent and/or metastatic non-ACC SGCs to find any potentially druggable target. Some histotypes may carry driving mutations that must be investigated and defined. For the rare cancers, access to a referral center is recommended to optimize the management of these patients.